Personal Selling dalam Memasarkan Jasa Penyelenggaraan Event Corporate - Septi Asifa Amalia; Anne Ratnasari (Bandung Conference Series: Communication Management, 2022)
Abstract. Various efforts have been made by the company, especially companies engaged in the event management service industry. Of the many existing event organizer businesses, various efforts to get clients are carried out with various forms of marketing communications to make them more recognized and superior. The author is interested in marketing communication efforts through personal selling carried out by one of the event organizers in Bandung in organizing corporate events. The purpose of this study was to determine the personal selling activities carried out by Vecha Activation in providing services for organizing corporate events. It is hoped that in this study, it can provide more knowledge for other researchers regarding personal selling activities in marketing services, it is also expected for Vecha Activation to improve promotions and event concepts. The research method used in this study is a qualitative research method with a case study approach and a constructivist paradigm. Through this research method, the author wants to know the personal selling process carried out by Vecha Activation in marketing its services. Data collection techniques used are interviews, observation, documentation and literature study. The research subjects are the CEO of Vecha Activation as the owner, staff of the marketing division of Vecha Activation, and clients of Vecha Activation. The data analysis technique used by the author is a data analysis technique according to Miles and Huberman. The results of the study found that the forms of personal selling carried out were retail selling, field selling and executive selling. Furthermore, there are several stages of personal selling that are carried out, namely determining clients according to market segmentation, seeking information and client approaches, mining insights, percentages, build adjust and iterate, and closing. Barriers faced when doing personal selling are disagreements, minimal relationships with various companies and lack of ability to assess potential clients. Efforts to overcome these obstacles are referring to TOR (Term of Reference), sending canvassing emails and monitoring client activities through social media and company-owned websites. And the uniqueness of the concept found is that there are gimmick performances and the advantages of visualization and digitization. Abstrak. Berbagai upaya dilakukan perusahaan khususnya perusahaan yang bergerak pada bidang industri jasa penyelenggaraan event. Dari sekian banyak usaha event organizer yang ada, berbagai upaya untuk mendapatkan klien dilakukan dengan berbagai bentuk komunikasi pemasaran agar semakin dikenal dan unggul. Penulis tertarik pada upaya komunikasi pemasaran melalui personal selling yang dilakukan oleh salah satu event organizer di Bandung dalam menyeleggarakan event corporate. Tujuan penelitian ini dilakukan untuk mengetahui kegiatan personal selling yang dilakukan oleh Vecha Activation pada penyediaan jasa penyelenggaraan event corporate. Maka diharapkan dalam penelitian ini, dapat memberikan pengetahuan yang lebih untuk peneliti lain mengenai kegiatan personal selling dalam memasarkan jasa, juga diharapkan bagi Vecha Activation untuk meningkatkan promosi dan konsep acara. Metode penelitian yang digunakan pada penelitian ini ialah metode penelitian kualitatif dengan pendekatan studi kasus dan paradigma konstruktivis. Melalui metode penelitian ini, penulis ingin mengetahui proses personal selling yang dilakukan Vecha Activation dalam memasarkan jasanya. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dokumentasi dan studi kepustakaan. Subjek penelitian yaitu CEO Vecha Activation sebagai pemilik, staff divisi marketing Vecha Activation, dan klien Vecha Activation. Teknik analisis data yang digunakan penulis adalah teknik analisi data menurut Miles dan Huberman. Hasil penelitian yang ditemukan adalah bentuk personal selling yang dilakukan adalah retail selling, field selling dan executive selling. Selanjutnya ada beberapa tahapan personal selling yang dilakukan yaitu menentukan klien sesuai segmentasi pasar, mencari informasi dan pendekatan klien, insight mining, persentasi, build adjust and iterate, dan closing. Hambatan yang dihadapi saat melakukan personal selling adalah adanya ketidaksepakatan, minim relasi dengan berbagai perusahaan dan kurangnya kemampuan dalam menilai klien berpotensial. Upaya mengatasi hambatan tersebut adalah mengacu pada TOR (Term of Reference), mengirimkan canvassing email dan memantau aktivitas klien melalui media sosial dan website milik perusahaan. Serta keunikan pada konsep yang ditemukan adalah terdapat pentas gimmick serta keunggulan visualisasi dan digitalisasi.